THE TRAINING OF TEACHER LIBRARIANS IN COMPARISON WITH PROFESSIONAL LIBRARIANS IN MALAYSIA - Raja Yaacob, Raja Abdullah; Samsuri, Saidina Omar (Malaysian Journal of Library and Information Science, 2003)
A recognition of the crucial role of libraries to education has led to the establishment of school libraries and resource centres in almost all school systems in Malaysia. Each school has conventionally allocated a teacher to take charge of the administration and services of the libraries in addition to the teaching load they have to accomplish. For the past five decades, this system has been going on and it would be interesting to study how the teachers acquired the training in the library management and services. Although there have been calls for the establishment of well developed school libraries headed by professionally trained librarians, the current practice of training teachers to take charge of the library is widely done. The reengineering and the creation of new information programmemess to comply with the new demands of ICT have made it imperative for upgrading of the training for the teacher librarians. This paper attempts to describe the current training for teacher-librarians and the prospects of providing a more advanced training as needed by the job market.